Metabolism engineering of Paenibacillus polymyxa for productive production of 2,3-butanediol - Muravska, A.H. (Problems of Environmental Biotechnology, 2023)
The purpose of the work is to review recent studies of genetic modifications of the metabolism of P. polymyxa to increase its productivity in the production of 2,3-butanediol.